2021
DOI: 10.7554/elife.63910
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and molecular evolution across 10,000 generations in laboratory budding yeast populations

Abstract: Laboratory experimental evolution provides a window into the details of the evolutionary process. To investigate the consequences of long-term adaptation, we evolved 205 Saccharomyces cerevisiae populations (124 haploid and 81 diploid) for ~10,000 generations in three environments. We measured the dynamics of fitness changes over time, finding repeatable patterns of declining adaptability. Sequencing revealed that this phenotypic adaptation is coupled with a steady accumulation of mutations, widespread genetic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
81
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(93 citation statements)
references
References 70 publications
10
81
1
1
Order By: Relevance
“…Further, after 50,000 generations of purely asexual evolution, (Tenaillon et al, 2016) found an average fitness increase of ~1.7-fold amongst all replicate Escherichia coli populations during adaptation to nutrient limitation. These comparisons suggest that the presence of recombination and high levels of standing variation lead to much larger fitness gains than are normally seen in experiments with less variation and/or no recombination, at least over short bursts of evolution in a novel environment, consistent with early studies that have more directly made this observation (Johnson et al, 2021).…”
Section: Fitness Increased Substantially After 12 Weeks Of Evolutionsupporting
confidence: 76%
See 2 more Smart Citations
“…Further, after 50,000 generations of purely asexual evolution, (Tenaillon et al, 2016) found an average fitness increase of ~1.7-fold amongst all replicate Escherichia coli populations during adaptation to nutrient limitation. These comparisons suggest that the presence of recombination and high levels of standing variation lead to much larger fitness gains than are normally seen in experiments with less variation and/or no recombination, at least over short bursts of evolution in a novel environment, consistent with early studies that have more directly made this observation (Johnson et al, 2021).…”
Section: Fitness Increased Substantially After 12 Weeks Of Evolutionsupporting
confidence: 76%
“…Under this asexual isogenic paradigm forces such as historical contingency (Toprak et al, 2011), genetic parallelism at the level of genes but not (except for rare exceptions, see (Toprak et al, 2011)) specific mutations (Tenaillon et al, 2012;Toprak et al, 2011), and diminishing returns epistasis (Toprak et al, 2011;Wang et al, 2016) matter a great deal to the evolutionary process. Similar studies in asexual isogenic diploids have shown that ploidy can influence the dynamics of adaptation, with diploids often adapting more slowly than haploids, likely due to the effects of Haldane's sieve (Fisher et al, 2018;Gerstein et al, 2014;Johnson et al, 2021;Marad et al, 2018;Sellis et al, 2016;Sellis et al, 2011;Zeyl et al, 2003). Diploids also appear to accumulate more potentially deleterious mutations (increased mutational load), and continue to adapt longer than haploids, likely due to the effects of mitotic recombination (Forche et al, 2011;Gerstein et al, 2014;Johnson et al, 2021).…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Kozela and Johnston [8] examined the effects of growth-limiting salt stress on mutational variation and the mutation rate. Johnson et al [9] performed a large-scale evolutionary experiment in three environments and identified several features of adaptation thought to be common across many species. Other fungal species are rarely used in experimental evolution, although fungi, especially microfungi, are generally good experimental subjects due to their relatively short generation times, compact genomes, and large effective population sizes compared to other eukaryotes.…”
Section: Introductionmentioning
confidence: 99%
“…Whether the multiple unlinked genes underlying a complex adaptation depend on each other to this degree is less well understood. Laboratory evolution has allowed genomic surveys (Blount et al, 2012; Good et al, 2017; Johnson et al, 2021; Kryazhimskiy et al, 2014) and, in some cases, experimental validation (Chou et al, 2011; Khan et al, 2011) of interactions between adaptive genes. Testing these principles in the context of evolution from the wild has posed a key challenge (although see Marcusson et al, 2009).…”
Section: Introductionmentioning
confidence: 99%